Interest and Utility of MC1R Testing for Melanoma Risk in Dermatology Patients with a History of Nonmelanoma Skin Cancer. (31st July 2022) - Hay, Jennifer L.; Lee, Erica H.; Christian, Stephanie N.; Schofield, Elizabeth; Hamilton, Jada G.; Yang, Ciyu; Hedayati, Bobak; Sadeghi, Keimya; Robson, Mark E.; Halpern, Allan; Zhang, Liying; Orlow, Irene
Abstract : Public access to genetic information is increasing, and community dermatologists may progressively encounter patients interested in genetic testing for melanoma risk. Clarifying potential utility will help plan for this inevitability. We determined interest and uptake of genetic risk feedback based on melanocortin receptor gene ( MC1R ) variants, immediate (two weeks) responses to risk feedback, and test utility at three months in patients (age ≥ 18, with a history of nonmelanoma skin cancer). Participants ( N  = 50) completed a baseline survey and were invited to consider MC1R testing via the study website. Testing interest and uptake were assessed through registration of test decision, request of a saliva test kit, and kit return (all yes/no). Immediate responses to risk feedback included feedback-relevant thoughts, emotions, communication, and information seeking after result receipt; test utility outcomes included family and physician communication and information seeking. Results indicated good retention at both time points (76%; 74%). Half (48%) logged onto the study website, and of these, most (92%) chose testing and (95%) returned a saliva sample. After two weeks, most (94%) had read all the risk feedback information and distress was low ( M  = 8.81, 7–28, SD = 2.23). Many (69%) had talked with their family about the results. By three months, most had spoken with family (92%) and physicians (80%) about skin cancer risk. Physician communication was higher (70%) in those tested versus those not tested (40%, p = 0.02 ). The substantial interest and promising outcomes associated with MC1R genetic testing in dermatology patients inform intervention strategies to enhance benefits and minimize risks of skin cancer genetic testing.